Evaluation of cartridge-based nucleic acid amplification test for diagnosis of tuberculosis in children in various body fluids - Agarwal, Dipti; Bhatia, Rakesh; Dayal, Rajeshwar; Khera, Rhythm; Narayan, Shamrendra; Goyal, Ankur (Indian Journal of Child Health, 2019)
Introduction: The paucibacillary nature presents a major challenge in the diagnosis of tuberculosis (TB) in children. The utilization of cartridge-based nucleic acid amplification test (CBNAAT) for the diagnosis of TB presents itself with added advantages such as detection to resistance to rifampicin and short turnaround time. Objectives: The aim of the study is to evaluate the diagnostic yield of CBNAAT in various body fluids and to compare with BACTEC-MGIT 960 and acid-fast bacilli (AFB) microscopy in children with suspected TB and to see the prevalence of rifampicin resistance in the study population using CBNAAT. Materials and Methods: This cross-sectional study included participants <14 years with suspected TB. Gastric aspirate samples obtained from pulmonary TB cases and body fluid specimens obtained from extrapulmonary TB cases were processed for the detection of Mycobacterium tuberculosis (MTB) using CBNAAT, BACTEC-MGIT 960, and AFB microscopy. The results obtained using CBNAAT were compared to other laboratory tests using an appropriate statistical method. Results: Fifty patients diagnosed with TB (34 pulmonary, 10 pleural effusion, and 6 abdominal) were included in the study, and clinical fluid specimens obtained from study participants were processed for the detection of MTB. Out of 34 gastric aspirate samples, 28 (82%) were positive by CBNAAT which was statistically higher than BACTEC-MGIT 960 (P < 0.05). Among extrapulmonary TB cases, only 2 pleural fluid specimens were positive by CBNAAT, whereas BACTEC-MGIT 960 and AFB microscopy could not detect MTB. Out of 34, 4 (11.76%) patients with newly diagnosed pulmonary TB were found to be rifampicin resistant using CBNAAT. Conclusions: CBNAAT showed promising results as a diagnostic tool in detecting MTB and rifampicin resistance in pulmonary TB using gastric aspirate. It, however, did not show good results in children with extrapulmonary TB in the clinical fluid specimen. The present study also showed the presence of high rifampicin resistance in treatment naïve pulmonary TB patients.